Group B streptococcal infective endocarditis in a young non-pregnant female with rheumatic heart disease - A Case Report - Alles, M.; Jayatilleke, K.; Chandrasiri, S.; Pathirage, S.; Janaka, K.V.C.; Herath, J.; Amarasena, N.; Wariyapola, D. (Sri Lankan Journal of Infectious Diseases, 2019)
Group B Streptococcus (GBS) is a rare cause of infective endocarditis in adults associated with a high mortality rate due to the frequent occurrence of local and systemic complications. Here we report a case of infective endocarditis (IE) in a young non-pregnant female with a history of rheumatic heart disease (RHD) who presented with a short history of fever, shortness of breath and constitutional symptoms. GBS was isolated from a single blood culture along with echocardiographic findings of a cardiac vegetation and ophthalmologic findings of a Roth spot. Based on the Modified Duke Criteria, a definitive diagnosis of infective endocarditis was made. She was treated with a prolonged course of intravenous (IV) ceftriaxone, with gentamicin being added to the regimen, following which she made a complete recovery.
Keywords: Infective endocarditis; Roth spot; Group B Streptococcus; Bacteraemia; Rheumatic heart disease